The application of multi-phase power distribution line with pure energy conversion - Can, Erol (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper discusses the power transmission of a six-phase power line with a six-phase LPWM inverter. The 20 km long line with six-phase is formed to be fed from the 6-phase multi-level inverter. The structure of the line and the elements of the power line are given in the design phase. After that, mathematical analysis of the power line is done to present information on the line structure and the relationship between the variables of the line. In the application stage, the described line is operating in Matlab Simulink. The input voltage of the line, the voltage of the RC parallel filter on the line and the voltage of the 1MW load on the line are measured. Six phase flux of the power is measured according to b2 and b4 bus points. Harmonic distortion of created voltages is measured. The harmonic distortion of the voltage on the Z2 impedance is 0.12%. This level of deterioration is well below the international standard of 5% and is an ideal result for loads that need a pure multi-phase magnetic field. 6-phase voltage is measured at 244V amplitude on a 6-phase load with 1 MVA power connecting the secondary side of the transformer. Then, the distortion of this voltage is close to zero. This result is highly desirable for a load on the power line. Based on the results obtained, the power is transmitted over a 20 km long line with high quality successfully.